Clinical‑pathological findings induced by Histophilus somni isolated in subacute cardiac death in feedlot cattle - de Yaniz, María Guadalupe (2022)
The purpose of this report is to provide information about the different presentations of cardiac and extra-cardiac histophilosis and, to assess the antimicrobial (ATM) susceptibility of Histophilus somni isolated from these cardiac lesions to different ATM agents commonly used for treating bovine bacterial respiratory pathogens. Eight feedlot calves, which died after suffering from food rejection, apathy, hyperthermia, cough and nasal mucous discharge, and lack of response to ATM therapy, were studied. Cardiac lesions observed at necropsy included valvular/mural endocarditis, myocardial infarction, and necrotizing myocarditis, miliar non-suppurative myocarditis, myocardic necrotic sequestrum, and/or pericarditis. Histopathological, bacteriological and molecular studies confirmed the presence of a fastidious microorganism in the affected organs. H. somni showed no resistance to most ATM tested (ceftiofur, gamithromycin, enrofloxacin, florfenicol, tilmicosin). The results obtained in this study confirmed that H. somni was the main cause of the subacute cardiac lesions associated with hyperthermia, apathy and respiratory signs observed in cattle examined in this research. These presentations must be considered by veterinary practitioners in order to establish a rational therapeutic.